Balloon Angioplasty For Symptomatic Central Venous Stenosis In Patients With Upper Limb Arteriovenous Fistula Dialysis Access: A Case Report - Delta Kurnia; Ramzi Asrial; Andrea Valentino; Ade Wirdayanto; Finanta Okmayura (Universitas Pahlawan Tuanku Tambusai, 2026)
Central venous stenosis usually occurs as a complication of central venous catheterization and significantly complicates dialysis through arteriovenous fistula in the ipsilateral limb. If a functioning arteriovenous fistula is present distal to such an obstruction, massive venous hypertension may occur producing arm edema, ulceration, and tissue loss. 17-year-old female complaining of swelling on the left upper limb since 1 month ago, getting bigger, the swelling is reddish in color and feels hot. The patient has a history of Chronic Kidney Disease for 3 years and is routinely dialyzed 2 times a week. After 2 years of Arteriovenous Shunt installation and Catheter Double Lumen, swelling appeared on the left upper limb for the first time. Physical examination revealed swelling and redness of the left upper limb. Performed venography seen total occlusion of the left central vein. Performed balloon angioplasty. Swelling and redness in the left upper limb have decreased after ballooning is taken. Central venous stenosis leading to ipsilateral Arteriovenous Shunt dysfunction and hemodialysis inefficiency can be treated successfully with balloon angioplasty.